SELF-DETERMINATION, THE CHAGOS ADVISORY OPINION AND THE CHAGOSSIANS. Issue 1 (January 2020) - Allen, Stephen
Abstract: In its Chagos Advisory Opinion, the International Court of Justice (ICJ) ruled that the UK's detachment of the Chagos Archipelago from the colony of Mauritius on the eve of independence constituted a violation of customary international law (CIL). This article analyses the Court's approach to establishing the emergence and content of the right to self-determination in this frustrated case of decolonisation. It goes on to examine the argument that self-determination's peremptory character has decisive consequences in this specific context—a contention which found favour with several judges in their Separate Opinions. The article explores the extent to which the claims and counterclaims, made during the advisory proceedings, turned on countervailing readings of not only the key sources of custom but also of the principle of inter-temporal law. The final sections consider the significance of the Chagos Opinion for the Chagossians, both in relation to the Archipelago's resettlement and for their outstanding appeal in the UK courts (where the European Convention on Human Rights performs a pivotal role).